Leprosy: ancient disease remains a public health problem nowadays - Leandro Fonseca Noriega; Nilton Di Chiacchio; Angélica Fonseca Noriega; Gilmayara Alves Abreu Maciel Pereira; Marina Lino Vieira (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Despite being an ancient disease, leprosy remains a public health problem in several countries -particularly in India, Brazil and Indonesia. The current operational guidelines emphasize the evaluation of disability from the time of diagnosis and stipulate as fundamental principles for disease control: early detection and proper treatment. Continued efforts are needed to establish and improve quality leprosy services. A qualified primary care network that is integrated into specialized service and the development of educational activities are part of the arsenal in the fight against the disease, considered neglected and stigmatizing.